Tingkat Difusi-Adopsi Inovasi Biogas di Kecamatan Lembang Kabupaten Bandung Barat - Nurul Dwi Novikarumsari; Siti Amanah; Basita Ginting Sugihen (Jurnal Penyuluhan, 2014)
This study aims to analyse the household characteristics of dairy farmer, perception of biogas innovation, access of information, the meeting with extension workers and factors affecting biogas diffusion and adoption in Lembang Sub District. Lembang Sub District has a potential of 4 149 dairy farmer households as prospected biogas adopters. Suntenjaya and Cibodas villages were selected as the research sites. All of the population member (266 households) were the research respondents. Questionnaires consist of four independent variables include dairy farmers characteristic, perception of biogas, access of information, and the meeting with extension workers were used to collect primary data. Rank Spearman correlation test was used to analyse the data. Research results shows that motivation, complexity, compatibility, and observability has positive correlation with speed of adoption; and dairy farmers experiences, relative advantage, and and triability has positive correlation with diffusion; the access of information and meeting with extension workers do not correlate with biogas diffusion-adoption since the farmers has involved in the biogas program from an international foundation.Keywords: diffusion, adoption, biogas, perception, inovation